PENGARUH UKURAN PERUSAHAAN DAN AUDIT TENURE TERHADAP KUALITAS AUDIT PADA PERUSAHAAN SEKTOR KONSUMEN PRIMER - Araswati; Nurlaelah; Herlina (Universitas La Tansa Mashiro, 2024)
Audit quality is all the possibilities (probability) that the auditor when auditing the client's financial statements can determine violations that occur in the client's accounting system and report them in the audited financial statements, audit quality is measured using Kap Bigfour and Non bigfour. Companies audited using Bigfour hood will result in increased company size and more audit quality. This study aims to test and analyze the effect of Company Size and Audit Ternure on Audit Quality in primary consumer sector companies listed on the Indonesia Stock Exchange in 2017-2021. The data used is secondary data with the research method used, namely quantitative methods. The population and this study amounted to 103 primary consumer sector companies and the sample taken using purposive sampling was 24 companies. The analysis technique used is Logistic Regression Analysis using SPSS 25 software. The results of the analysis conducted show that partially Company Size (Ln = Total Assets) has a significant effect on Audit Quality, so H1 is accepted. Audit tenure (Auditor Engagement with Client / Issuer) partially has no effect on audit quality, so H2 is rejected. Meanwhile, simultaneously Company Size and Audit Tenure affect audit quality, so H3 is accepted..